La peinture du XXe siècle du Musée de Picardie. : Collections Amiens, Musée de Picardie. - Bouquin, Laurence; Huchard, Viviane; Viéville, Dominique (Amiens : Musée de Picardie, 1992)
Vuillard, Edouard ; Fautrier, Jean ; Picabia, Francis ; Balthus ; Manessier, Alfred ; Masson, André ; Dubuffet, Jean ; Jorn, Asger ; Sutherland, Graham ; Picasso, Pablo ; Hélion, Jean ; Bacon, Francis ; LeWitt, Sol
boek